Emotion regulation during adolescence: Antecedent or outcome of depressive symptomology?. (March 2019) - De France, Kalee; Lennarz, Hannah; Kindt, Karlijn; Hollenstein, Tom
Consistently, moderate to strong correlations between emotion regulation and depressive symptomology are well documented. This relationship is most often conceptualized as unidirectional, in that poor emotion regulation acts as a pre-existing risk factor for depressive symptomatology. However, explicit examinations of the direction of this relationship have been limited, and support for a directional relation between emotion regulation and psychopathology has been inconsistent. Moreover, the majority of the research exploring these associations relies on adult participants and the studies that have examined emotion regulation and depression in adolescents have relied almost exclusively on cross-sectional data. As a replication and extension of work that has been done by others, the current study assessed Suppression and Reappraisal use and Depressive Symptoms in 1343 adolescents (Mean age = 12.9 years, SD = 0.85) who completed assessments of emotion regulation and depressive symptoms four times over two years. Results indicated that only Suppression but not Reappraisal was concurrently correlated with Depressive Symptoms. Moreover, a correlated slopes analysis showed that within-subject changes in use of Suppression, but not Reappraisal, were associated with within-subject changes in Depressive Symptoms over time. Finally, a cross-lag panel analysis showed that while Depressive Symptoms were predictive of future Suppression use, Suppression use did not predict later Depressive Symptoms. Therefore, while Suppression and Depressive Symptoms seem to be associated during adolescence, associations between reappraisal and depressive symptomology were not present in the current study. Moreover, despite previous evidence supporting emotion regulation as a risk factor for depression, suppression may be the outcome, rather than the antecedent, of depressive symptoms during adolescence.